Epigenetic Regulation of Autophagy: A Path to the Control of Autoimmunity - Hargarten, Jessica C.; Williamson, Peter R. (Frontiers in Immunology, 2018)
Autoimmune diseases are a significant cause of debilitation and mortality globally and are in need of cost-effective therapeutics. Autophagy is a cellular pathway that facilitates immune modulation involved in both pathogen control as well as autoimmunity. Regulation is multi-factorial and includes a number of epigenetic pathways which can involve modification of DNA-binding histones to induce autophagy-related mRNA synthesis or micro RNA and decapping-associated mRNA degradation which results in autophagy suppression. Appreciation of epigenetic-based pathways involved in autophagy and autoimmunity may facilite application of a burgeoning group of epigenetic pharmaceuticals to these important diseases.